Systemic epothilone D improves hindlimb function after spinal cord contusion injury in rats - Sandner, Beatrice; Puttagunta, Radhika; Motsch, Melanie; Blesch, Armin; Weidner, Norbert (Experimental neurology, 2018)
Following a spinal cord injury (SCI) a growth aversive environment forms, consisting of a fibroglial scar and inhibitory factors, further restricting the already low intrinsic growth potential of injured adult central nervous system (CNS) neurons. Previous studies have shown that local administration of the microtubule-stabilizing drug paclitaxel or epothilone B (Epo B) reduce fibrotic scar formation and axonal dieback as well as induce axonal growth/sprouting after SCI. Likewise, systemic administration of Epo B promoted functional recovery. In this study, we investigated the effects of epothilone D (Epo D), an analog of Epo B with a possible greater therapeutic index, on fibrotic scarring, axonal sprouting and functional recovery after SCI. Delayed systemic administration of Epo D after a moderate contusion injury (150kDyn) in female Fischer 344 rats resulted in a reduced number of footfalls when crossing a horizontal ladder at 4 and 8weeks post-injury. Hindlimb motor function assessed with the BBB open field locomotor rating scale and Catwalk gait analysis were not significantly altered. Moreover, formation of laminin positive fibrotic scar tissue and 5-HT positive serotonergic fiber length caudal to the lesion site were not altered after treatment with Epo D. These findings recapitulate a functional benefit after systemic administration of a microtubule-stabilizing drug in rat contusion SCI.
Gesehen am 17.05.2019